2003
DOI: 10.1063/1.1621713
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of fluorine-based high-density plasma etching of anisotropic silicon trenches with oxygen sidewall passivation

Abstract: Level set approach to simulation of feature profile evolution in a high-density plasma-etching systemThe kinetics of high aspect ratio, anisotropic silicon etching in a SF 6 -O 2 plasma is investigated with a combination of Monte Carlo simulations and inductively coupled plasma etching experiments. The spontaneous reaction of atomic fluorine is dominant at room temperature and Knudsen transport of the radicals is the only limitation in narrow structures. At low temperatures ͑typically between Ϫ125 and Ϫ95°C͒ o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 29 publications
(25 reference statements)
0
26
0
Order By: Relevance
“…Under these conditions, the etching rates are very low. The comparison between these results and experiments performed in DIMES laboratory in the Netherlands [17] has shown that the best correlation is obtained with the trench T1. In this case, topography and the etching rates are very similar.…”
Section: Study With Oxygen: Evaluation Of the Redeposition Rate In A mentioning
confidence: 62%
See 2 more Smart Citations
“…Under these conditions, the etching rates are very low. The comparison between these results and experiments performed in DIMES laboratory in the Netherlands [17] has shown that the best correlation is obtained with the trench T1. In this case, topography and the etching rates are very similar.…”
Section: Study With Oxygen: Evaluation Of the Redeposition Rate In A mentioning
confidence: 62%
“…For the trench T1, an excellent mask transfer is obtained: the sidewalls are almost vertical without roughness. The vertical etching rate is about 3.5 mm/min which is closed to the experiments [17]. On the contrary, the properties of trench T2 are very modified and affected by the strong redeposition phenomenon.…”
Section: Study With Oxygen: Evaluation Of the Redeposition Rate In A mentioning
confidence: 99%
See 1 more Smart Citation
“…[6] There are some computational studies of SF 6 /O 2 plasmas but they do not explicitly refer to cryoetching. Blauw et al [15] investigated the kinetics of SF 6 Ryan and Plumb previously developed a model to describe the SF 6 /O 2 plasma chemistry and the etching of Si with these plasmas, [20] [ 21] In recent years, not only low-k dielectric cryoetching but also silicon cryoetching has gained increasing interest. The primary difficulty with SF 6 /O 2 cryogenic DRIE is the high sensitivity to the oxygen content and the substrate temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it is now possible with plasma etching process using high density plasma reactors such as Inductive Coupled Plasma (ICP) to transfer nanometer scale patterns from the mask to the substrate [1][2][3][4][5]. The success of the high aspect ratio pattern transfer without geometrical defects [6][7][8][9] (bowing, undercut, trenching,..) is tributary of a good understanding of the physical and chemical mechanisms of the plasma discharge and the surface kinetic processes. Some attempts of Si and III-V pattern transfer development like photonic crystals, deep trenches or mesa structures are achieved by plasma etching [10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%